CODE SWITCHING USED BY INTERNATIONAL TOURIST TO LOCAL PEOPLE IN SORAKE BEACH - Halawa, Eltinus (Universitas Nias Raya, 2023)
Code switching as one of the language events that often occurs in social interactions between speakers and interlocutors due to the ability of language users as bilinguals or multilingual. This research aimed to describe and to explain the types and the reasons of code switching occurrence between local people in Botohili Sorake Village and international tourists in Sorake Beach. The participants of this research were the international tourists (foreign tourist) in Sorake Beach. This research was conducted by utilized qualitative method with descriptive approach. The instruments applied in collecting data were the observation and interview. The data acquired were analyzed by using Miles and Huberman’s mode: 1) data condensation, 2) data displayed, and 3) conclusion drawing/verification. The results of this study indicate that the types of code switching used by international tourists (foreign tourist) in their interaction to local people in Sorake Beach, Botohili Sorake Village, Luahagundre District were: a) Inter-sentential Code Switching, b) Intra-sentential Code Switching. Thus, based on the results found, it can be concluded that the code switching in an interaction is very helpful for language users, both speakers and interlocutors in understanding and conveying messages or information. This study also reveals several reasons for the use of code switching in an interaction, none other than to avoid misunderstanding the meaning of language between the speakers and interlocutors and as an advantage, especially for bilingual. Briefly, it can be stated that code switching has an important role in a communication. However, although the presence and role of code switching is quite important in language, the researcher also suggests to language users to increase the ability to use language as communication tool, both in their own language and in other language.